DAM (Department of Agriculture Marketing ) information collection system : sample data , agriculture commodity prices - Rahman, Md. Mushfikur (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2005.